Kenaf Fibre Composites As Promising Green-Composites For Automotive Car Door Map Pocket Application - Yahaya, Saifudin Hafiz; Yaakob, Mohd Yuhazri; Abdullah, Abu; Husin, Mohd Amirhafizan; Kamarul, A.M.; Lau, S.T.W. (IJENS Publisher, 2018)
The utilisation of natural fibres in composite materials is expanding because of an enactment that constrains automotive makers to reuse and recycle materials,leading to an increase in bio-based materials substances in automotive applications.An experimental investigation was conducted to explore car door map pocket for PROTON Saga FL by using non-woven kenaf (N-W)and hybrid from non- oven/ woven fabric kenaf (HN-W/W).The Hand Lay-up Method followed by vacuum bagging process were used.The results revealed that L2 HN-W/W was the reasonable sample for car door map pocket due to its light weight,good tensile strength and flexural strength as compared to PP.It was also found that the tensile strength and flexural strength were improved by utilising woven kenaf fabric in composites.Result implications and future research directions were also presented.